2017
DOI: 10.1049/iet-cta.2016.1501
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control for pre‐compensated voltage mode controlled DC–DC converters

Abstract: This study introduces the use of model predictive control (MPC) to improve the performance of pre-compensated power supplies, and in particular of DC-DC converters, by dynamically modifying their output voltage reference. The importance of developing controllers for pre-compensated converters is twofold. First, the hierarchical structure is particularly useful when the primal controller is already coded, or hardware based, and cannot be changed. Second, the double-loop and, possible, multi-rate structure repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…The Generalized Proportional Integral (GPI) observer-based discrete MPC is designed in [32] to predict a lumped time-varying disturbances, and the MPC controller therein regulates the output voltage even the control input gain is not known precisely. The pre-compensated MPC scheme is proposed in [33,34], which can steer a reference voltage value to the primal controller dynamically, without modifying the primal control structure. However, it has to run at slower frequency than the primal controller to meet computational constraints, which limits the ability of the MPC controller.…”
Section: Introductionmentioning
confidence: 99%
“…The Generalized Proportional Integral (GPI) observer-based discrete MPC is designed in [32] to predict a lumped time-varying disturbances, and the MPC controller therein regulates the output voltage even the control input gain is not known precisely. The pre-compensated MPC scheme is proposed in [33,34], which can steer a reference voltage value to the primal controller dynamically, without modifying the primal control structure. However, it has to run at slower frequency than the primal controller to meet computational constraints, which limits the ability of the MPC controller.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the simulator in a lower level programming language, such as C, makes our algorithm very fast and results in microsecond running times. For the purpose of further speeding up the NMPC convergence, like in previous studies, the NMPC horizon was drastically decreased, even to the value N=2, and still provides sufficiently good transient performance with a small overshoot. For the high‐speed experimental implementations, the algorithm can be parallelized and implemented on FPGA or in ASIC.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the transient overshoot of the state variables during the transient process and after some disturbance in the circuit shows to be rather large. 13 In Cavanini et al, 14 a model predictive controller for the output voltage of the precompensated discretized DC-DC converter is calculated offline, and better performance than the standard voltage mode control (VMC) method is demonstrated. MPC for the reference values of the states of a DC-DC boost converter with a constant switching frequency has been suggested in Cheng et al, 15 where the authors demonstrate that the suggested approach is suitable for real-time implementation for converters with a switching period of T S = 50 s. Comparing with the work of Cheng et al 15 related to the design of MPC for boost converters, our work is modular, and it does not depend on the DC-DC converter's design.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are system dependent and add complexity to the design. It is reported that the performance improvement is achieved by using boundary layer control [27][28][29], adaptive nonlinear control [30], model predictive control [31][32][33], and a time delayed based robust controller [34]. However, these techniques are not completely parameter independent and require some knowledge of the system specifications like inductance of the coil and capacitance of the filter stage.…”
Section: Introductionmentioning
confidence: 99%